The Influence of Budget Participation and Accounting Information Systems on Managerial Performance with Organizational Culture and Work Motivation as Moderating Variables - Khosyiah; Muhamad Taqi; Munawar Muchlish (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the effect of budget participation and accounting information systems on managerial performance with organizational culture and work motivation as moderating variables. This research uses quantitative research with a survey approach by distributing questionnaires. The population in the study were work unit managers or structural officials at the Regional Apparatus Organization (OPD) of Cilegon City, with a total population of 449 people in this study. The sample was selected based on certain criteria so that it could support this research, namely 175 people (35 OPD). The data analysis technique used is the Structural Equation Model (SEM) method using WarpPLS 8.0 software, which ends with a hypothesis testing process. Based on data analysis, the results obtained are that (1) Budget Participation has a positive and significant effect on Managerial Performance. (2) Accounting Information Systems have a positive and significant effect on Managerial Performance. (3) Organizational Culture moderates the influence of Budget Participation on Managerial Performance. (4) Work Motivation does not moderate the influence of Budget Participation on Managerial Performance. (5) Organizational Culture moderates the influence of Accounting Information Systems on Managerial Performance. (6) Work Motivation does not moderate the influence of Accounting Information Systems on Managerial Performance